2021
DOI: 10.1016/j.ijcard.2021.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness and safety of sacubitril/valsartan in heart failure: A systematic review

Abstract: Background: PARADIGM-HF demonstrated superiority of sacubitril/valsartan (sac/val) over enalapril in patients with heart failure with reduced ejection fraction (HFrEF). However, patients in clinical practice may differ in their characteristics and overall risk compared with patients in clinical trials, and additional outcomes can be observed in real world (RW). Hence, a systematic review was conducted to identify and describe RW data on sac/val. Methods: RW studies evaluating the effects of sac/val in adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
(61 reference statements)
10
38
0
Order By: Relevance
“…Furthermore, there are numerous real-world studies looking at hHF with the initiation of sacubitril/valsartan, with 5 studies comparing hHF before and after initiation of sacubitril/valsartan. 16 These study results were consistent with our data, showing a 5.4% to 15% reduction in hHF over a period of 3 to 7.4 months. In terms of all-cause hospitalizations, 3 of the 4 studies that reported all-cause hospitalization data before and after initiation of sacubitril/valsartan showed a significant reduction ranging from 14.5% to 18%.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there are numerous real-world studies looking at hHF with the initiation of sacubitril/valsartan, with 5 studies comparing hHF before and after initiation of sacubitril/valsartan. 16 These study results were consistent with our data, showing a 5.4% to 15% reduction in hHF over a period of 3 to 7.4 months. In terms of all-cause hospitalizations, 3 of the 4 studies that reported all-cause hospitalization data before and after initiation of sacubitril/valsartan showed a significant reduction ranging from 14.5% to 18%.…”
Section: Discussionsupporting
confidence: 93%
“…The new SAC/VAL users in this study had significantly lower rates of all-cause hospitalizations and the composite of HF hospitalization or ER visits than the new ACEi/ARB users; this was true in the analyses of both total rates and time to first event. These results were similar to those observed in a systematic literature review of real-world studies, wherein studies comparing SAC/VAL with ACEi/ARB in patients with HFrEF (previously treated or naïve to ACEi/ARB) reported a significantly lower risk of all-cause hospitalization with SAC/VAL [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…Since the introduction of ARNI, studies assessing the benefit and risk of ARNI in real-world situation have increased [ 12 ]. For Asian population, there are currently 6 published studies.…”
Section: Discussionmentioning
confidence: 99%